Cellulitis and erysipelas - Morris, Andrew D (BMJ Publishing Group, 2008)
INTRODUCTION: Cellulitis is a common problem, caused by spreading bacterial inflammation of the skin, with redness, pain, and lymphangitis. Up to 40% of affected people have systemic illness. Erysipelas is a form of cellulitis with marked superficial inflammation, typically affecting the lower limbs and the face. The most common pathogens in adults are streptococci and Staphylococcus aureus. Cellulitis and erysipelas can result in local necrosis and abscess formation. Around a quarter of affected people have more than one episode of cellulitis within 3 years. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical questions: What are the effects of treatments for cellulitis and erysipelas? What are the effects of treatments to prevent recurrence of cellulitis and erysipelas? We searched: Medline, Embase, The Cochrane Library and other important databases up to May 2007 (BMJ Clinical Evidence reviews are updated periodically, please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 14 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review we present information relating to the effectiveness and safety of the following interventions: antibiotics, comparative effects of different antibiotic regimens, duration of antibiotics, and treatment of predisposing factors.